Digital speckle correlation for curved surfaces - Yamaguchi, Ichitou (Photonics Letters of Poland, 2012)
Displacement of speckles arising in the diffraction field of a laser-illuminated surface subject to homogeneous deformation is investigated by numerical simulations using a rough surface model represented by an assembly of point scatterers distributed randomly around its mean surface that can be arbitrary. The results obtained from the simulation are compared with those derived from analytical approach that assumes a plane mean surface. These will be useful for designing and constructing displacement and deformation measurement systems using digital correlation technique. Full Text: PDF References P. Jacquot and P. K. Rastogi,"Speckle motions by rigid-body movements in free-space geometry: an explicit investigation and extension to new cases", Appl. Opt., 18, 2022-2032(1979)[CrossRef] I. Yamaguchi,"Speckle displacement and decorrelation in the diffraction and image fields for small object deformation", Optica Acta, 28, 1359-1376 (1981)[CrossRef] I. Yamaguchi,"Holography, speckle, and computers", Opt. Lasers in Eng., 39, 411-429 (2003).[CrossRef] I. Yamaguchi,"Automatic measurement of in-plane tramslaton by speckle correlation using a linear image sensor", J. Phys.E, 19, 944-948(1986)[CrossRef] I. Yamaguchi, T. Takemori, T. and K. Kobayashi,"Stabilized and accelerated speckle strain gauge", Opt. Engin., 32, No. 3, 618-625 (1993).[CrossRef] I. Yamaguchi, "Holography and speckle in phase-shifting digital holography", Chinese Optics Letters, 7, 1104-1108 (2009)[CrossRef]